Role of Content and Influencer Attributes in Smartphone Purchase Intention - Rajagukguk, Josia; Heruwasto, Ignatius (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
Research Originality: This research extends the elaboration likelihood model (ELM) by examining the effect of long-form smartphone reviews on purchase intention on YouTube in Indonesia. Research Objectives: The study aimed to examine the role of content and influencer attributes in smartphone purchase intention in Indonesia. Research Method: The ELM was employed to analyze long-form smartphone reviews by tech-influencers. Data were obtained using an online survey distributed to 477 YouTube users who watched smartphone review content. Data were analyzed by using partial least squares structural equation modeling. Empirical Results: The study's results show that purchase intention is directly and positively associated with content originality, uniqueness, and informativeness, as well as with influencer’s trustworthiness and self-presence, with content uniqueness having the strongest effect. Influencer expertise, physical attractiveness, and social attractiveness indirectly affect purchase intention positively through content attributes. Implications: This study extends the ELM theory by examining social media and products reviewed by YouTube tech influencers. It provides managerial implications for influencers and companies in the technology sector, aiming to enhance their content quality, particularly uniqueness, and personal branding. JEL Classification: M30, M39, D91